2019
DOI: 10.1002/er.4556
|View full text |Cite
|
Sign up to set email alerts
|

Battery module thermal management based on liquid cold plate with heat transfer enhanced fin

Abstract: Summary Battery, as the main energy storage element, directly affects the performance of electric vehicle. Battery thermal management research is required as the battery performance influenced by temperature obviously. This article selects liquid cold plate with different heat transfer enhanced fins as the research object. The angle and length of fins are chosen as the variables. Computational fluid dynamics (CFD) methods and experiments are used in this research. The fin angle of 15°, 30°, and 45° and fin len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The results showed that the application of nanofluids and micro fins will increase the Nusselt number in the cold plate. Fu et al studied the effect of the length and angle of the inner flow fin on the cooling efficiency of the liquid‐cooled battery thermal management. Huo et al designed a mini‐channel liquid cold plate with different number of cooling channels to cool a rectangular Li‐ion battery by using computational fluid dynamics (CFD) method.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the application of nanofluids and micro fins will increase the Nusselt number in the cold plate. Fu et al studied the effect of the length and angle of the inner flow fin on the cooling efficiency of the liquid‐cooled battery thermal management. Huo et al designed a mini‐channel liquid cold plate with different number of cooling channels to cool a rectangular Li‐ion battery by using computational fluid dynamics (CFD) method.…”
Section: Introductionmentioning
confidence: 99%
“…However, the proposed thermal model based on the battery resistance still has insufficiencies. Some research regarded cell resistance to only be affected by the SOC or the temperature, and some even considered that the resistance was constant . In practice, there are obvious prediction errors if the thermal models based on the battery resistance do not fully covers the effects of the electrical and thermal parameters on the resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, there are obvious prediction errors if the thermal models based on the battery resistance do not fully covers the effects of the electrical and thermal parameters on the resistance. Moreover, in the existing literature on the thermal model of the pack, the influence of the temperature distribution in the pack on the branch current is not considered, leading to an error in calculating the branch current. Encouraged by the study gap mentioned above, this paper builds a new electrothermal model to improve the temperature prediction precision of an air‐cooled pack.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations